Variation in olive phenolics and antioxidant activity: influence of variety, location, and Bactrocera oleae attack - Belmahdi, Amina; Belattar, Hakima; Himour, Sara; Karbab, Ahlem; Charef, Noureddine (Environmental and Experimental Biology, 2024)
The olive tree (Olea europaea L.) holds significant economic importance, especially in the Mediterranean region, including Algeria, where diverse olive cultivars thrive due to the heterogeneous climate. This study presents a comparative analysis of phenolic and antioxidant properties in olive fruits from two Algerian cultivars, ‘Chemlal’ and ‘Sigoise’, focusing on the influence of different locations and varying attack rates of the olive fruit fly (Bactrocera oleae). Key biological parameters, including fruit weight, maturity index, and pest attack rates, alongside the content of phenolics, flavonoids, and condensed tannins were measured. Antioxidant activity was evaluated by measuring free radical scavenging, total antioxidant capacity, and ferric-reducing power. Significant variation in fruit characteristics and insect susceptibility between the two cultivars and locations was found. Cv. ‘Sigoise’ exhibited greater fruit weight but higher vulnerability to Bactrocera oleae attacks than cv. ‘Chemlal’. Fruits of cv. ‘Chemlal’ from Ain Arnat showed greater insect attack resistance and higher condensed tannin content. Antioxidant assays revealed that cv. ‘Chemlal’, especially from Ain Azel, had superior free radical scavenging and ferric-reducing ability, despite its lower phenolics content, indicating a robust antioxidant profile. This study demonstrates the potential of selecting and cultivating specific olive cultivars to optimize their health-promoting benefits and resistance to biotic stress. This underlines the need for tailored agronomic practices that consider genetic, environmental, and pest management factors for enhanced productivity and quality.